'Before reaching the last mile'- Knowledge, attitude, practice and perceived barriers related to tuberculosis directly observed therapy among ASHA workers in Central India: A mixed method study. Issue 4 (December 2017) - Singh, Akash Ranjan; Pakhare, Abhijit; Kokane, Arun M.; Shewade, Hemant Deepak; Chauhan, Ashish; Singh, Abhishek; Gangwar, Arti; Thakur, Prahlad Singh
Abstract: Introduction: Community-based direct observed treatment (DOT) providers are an important bridge for the national tuberculosis programme in India to reach the unreached. The present study has explored the knowledge, attitude, practice and barriers perceived by the community-based DOT providers. Methods: Mixed–methods study design was used among 41 community-based DOT providers (Accredited Social Health Activist (ASHAs)) working in 67 villages from a primary health center in Raisen district of Madhya Pradesh, India. The cross-sectional quantitative component assessed the knowledge and practices and three focus-group discussions explored the attitude and perceived barriers related to DOT provision. Result: 'Adequate knowledge' and 'satisfactory practice' related to DOT provision was seen in 14 (34%) and 13 (32%) ASHAs respectively. Only two (5%) received any amount of honorarium for completion of DOT in last 3 years. The focus-group discussions revealed unfavourable attitude; inadequate training and supervision, non-payment of honorarium, issues related to assured services after referral and patient related factors as the barriers to satisfactory practice of DOT. Conclusion: Study revealed inadequate knowledge and unsatisfactory practice related to DOT provision among ASHAs. Innovations addressing the perceived barriers to improve practice of DOT provision by ASHAs are urgently required.